A mixed-method (quantitative and qualitative) approach to measure women's empowerment in agriculture: evidence from Azad Jammu & Kashmir, Pakistan. Issue 1 (1st January 2023) - Aziz, Noshaba; Khan, Imran; Nadahrajan, Dinithambigai; He, Jun
ABSTRACT: There exists comprehensive literature on women's empowerment; however, studies on the measurement of empowerment in the agricultural context are scarce, particularly in Azad Jammu and Kashmir (AJK) Pakistan. In this paper, we used the Women's Empowerment in Agriculture Index (WEAI), which includes five domains, i.e. resources, production, income, leadership, and time, to measure women's empowerment in the agriculture sector. A survey of 600 rural women and 18 focus group discussions (FGDs) were conducted by using multi-stage sampling. The results show that about 72% of the women are disempowered, and attribute to low socio-economic conditions, i.e. they have limited access to resources and little leadership skills as rural women in AJK are not free to speak in public. The results further reveal that women are also disempowered in some other indicators, such as autonomy in production, income, and leisure time. So, based on the current findings, it is proposed that government should strengthen these areas through effective policies to improve the status of women.